ANALYSIS OF USER SATISFACTION LEVEL OF INTEGRATED LIBRARY SYSTEM (INLISLITE) SOFTWARE WITH END USER COMPUTING SATISFACTION (EUCS) METHOD - Asnawi, Asnawi; Maulidin, Ikhsan Khairul; Che Ibrahim, Hassan Bin; Mukhtaruddin, Mukhtaruddin (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to analyze the level of user satisfaction of the Integrated Library System (INLIS) Software in the Pidie Regency Library and Archives using the End User Computing Satisfaction (EUCS) method. The measurement of this satisfaction is based on five main dimensions, namely content, accuracy, format, ease of use, and timeliness. The methodology used is qualitative research with data collection methods, namely interviews and documentation. The number of informants in this study was 5 people consisting of 4 librarians and 1 head of the library service division. The results of the study indicate that the application content variables are in accordance with the needs of librarians, while the accuracy of the information provided by the application is reliable and trustworthy. In terms of format, INLISLite is considered very flexible and easy to use, with a user-friendly interface and intuitive menu placement, so that users do not feel tired. The ease of use of the application is considered high, covering the entire menu from acquisition to reporting. The application response time is also considered very fast, allowing librarians to access information efficiently. In addition, INLISLite's data security feature that limits user access to certain menus is considered reliable. Overall, the INLISLite application is considered to have met the needs of users, both librarians and users, and facilitates the work of librarians in carrying out daily tasks. Based on these findings, librarians at the Pidie Regency Library and Archives Service generally feel very satisfied with the use of the INLISLite application.